Associations of Genetic Variants of Methylenetetrahydrofolate Reductase and Serum Folate Levels with Metabolic Parameters in Patients with Schizophrenia - Chun-Hsin Chen (MDPI AG, 2021)
The one-carbon metabolism pathway is a suitable candidate for studying the genetic and epigenetic factors contributing to metabolic abnormalities in patients with schizophrenia. We recruited 232 patients with schizophrenia and analyzed their serum folate, vitamin B12, and homocysteine levels and metabolic parameters to investigate the associations of genetic variants of methylenetetrahydrofolate reductase (MTHFR) and folate levels with metabolic parameters. MTHFR C677T and MTHFR A1298C were genotyped. Results showed that MTHFR 677T allele carriers had lower levels of total cholesterol and low-density lipoprotein cholesterol than those with the 677CC genotype. Metabolic parameters did not differ between MTHFR 1298C and 1298AA carriers. Patients with a low folate level had a lower high-density lipoprotein cholesterol level than those with a normal folate level, but the effect disappeared after adjustment for age, sex, and types of antipsychotics used. We found significant interactions between MTHFR A1298C and the folate level status (low vs. normal) in terms of body mass index and waist circumference. In conclusion, genetic variants in one-carbon metabolism might play a role in antipsychotic-induced metabolic abnormalities. Prospective studies on drug-naïve, first-episode patients with schizophrenia are warranted to identify key regions of DNA methylation changes accounting for antipsychotic-induced metabolic abnormalities.